A REVIEW OF ONLINE LOAN REPAYMENT ABILITY TOWARDS THE LIFESTYLE AND FINANCIAL LITERACY OF GEN Z GENERATION - Simanjuntak, Novitasari (Lembaga Riset dan Pengembangan Sumatera Utara, 2025)
This study aimed to evaluate the impact of financial literacy and lifestyle on the capacity to repay online loan among Generation Z residing in Medan. The research method used was an associative quantitative survey approach, involving 100 participants selected using a purposive sampling technique. This research population consisted of all Gen Z residents in Medan according to data published by the Central Statistics Agency (BPS). The research findings indicate that financial literacy has a significant positive impact on respondents' capacity to repay online loan obligations. Furthermore, lifestyle also makes a significant positive contribution to repayment capacity. Multiple linear regression techniques were applied to assess the significance level of the influence of independent variables on changes in the dependent variable These two variables, both individually and collectively, have been shown to significantly contribute to explaining variations in Generation Z's ability to repay online loan re payment These findings emphasize the importance of improving financial literacy and adopting a wiser lifestyle so that the younger generation can better manage their finances in the face of the development of online loan repayment.